Elucidation of antioxidant compounds recovery capacity from Cam purple rice bran by different sustainable extraction techniques - Le Thi Kim Loan; Bui The Vinh; Ngo Van Tai (My University, 2024)
“Cam” rice is a pigmented rice with the purple color that was well known as local cultivar in Tien Giang province (Vietnam). The bran of this rice is usually not properly used; however, it contains rich antioxidants that could be utilized for demanding healthy and nutritional foods. This study is aimed to study the different green and sustainable extraction methods for rice bran’s antioxidants, including microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), ultrasound followed by microwave (U+MAE), microwave followed by ultrasound (M+UAE), and conventional method as the control. The results showed that high extraction efficiency was found when Cam rice bran was extracted with the aid of sustainable extraction techniques such as sonication or microwave. The study also reported that dual synergistic-assisted extraction presented a higher content of bioactive compounds and their antioxidant activities compared with single-assisted extraction. In addition, U+MAE was shown to have a higher capacity to extract and maintain antioxidant activities than M+UAE. This study provides the fundamental information for further application and optimization process of extract of antioxidant compounds from Cam rice bran, as source of antioxidant and nutraceutical ingredient.
Keywords: GABA and Rice Research